Targeting Neutrophils to Treat Acute Respiratory Distress Syndrome in Coronavirus Disease - Chiang, Chih-Chao; Korinek, Michal; Cheng, Wei-Jen; Hwang, Tsong-Long (Frontiers in Pharmacology, 2020)
This review describes targeting neutrophils as a potential therapeutic strategy for acute respiratory distress syndrome (ARDS) associated with coronavirus disease 2019 (COVID-19), a pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Neutrophil counts are significantly elevated in patients with COVID-19 and significantly correlated with disease severity. The neutrophil-to-lymphocyte ratio can serve as a clinical marker for predicting fatal complications related to ARDS in patients with COVID-19. Neutrophil-associated inflammation plays a critical pathogenic role in ARDS. The effector functions of neutrophils, acting as respiratory burst oxidants, granule proteases, and neutrophil extracellular traps, are linked to the pathogenesis of ARDS. Hence, neutrophils can not only be used as pathogenic markers but also as candidate drug targets for COVID-19 associated ARDS.